2017
DOI: 10.5539/ass.v13n5p165
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of Affective Organizational Commitment in the Relationship between Organizational Justice and Organizational Citizenship Behavior: A Conceptual Model

Abstract: A literature review revealed that the effect of organizational justice on organizational citizenship behavior (OCB) had been heavily examined as an overall relationship. However, there is a lack of research that examined the effect of organizational justice dimensions on OCB via affective organizational commitment as a mediator. Therefore, this research is an attempt to provide a value theoretical model that explains the relationships between dimensions of organizational justice and OCB as well as tries to des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
1
6
0
2
Order By: Relevance
“…More recently, Batool's (2013) study in public sector banks of Peshawar, Pakistan also reported similar results. Similar results have also been reported by different researchers in their studies (Khan and Rashid, 2015;Alzayed et al, 2017). This study uniquely adds credibility to widely held beliefs and some scholarly findings that the notion of employee commitment can greatly facilitate the voluntary behaviors and lead to positive perceptions about fairness of organizational processes (Brockner et al, 2001;Begley et al, 2002).…”
supporting
confidence: 89%
“…More recently, Batool's (2013) study in public sector banks of Peshawar, Pakistan also reported similar results. Similar results have also been reported by different researchers in their studies (Khan and Rashid, 2015;Alzayed et al, 2017). This study uniquely adds credibility to widely held beliefs and some scholarly findings that the notion of employee commitment can greatly facilitate the voluntary behaviors and lead to positive perceptions about fairness of organizational processes (Brockner et al, 2001;Begley et al, 2002).…”
supporting
confidence: 89%
“…The concept of OCB was coined by Organ [20] (p. 4) as "behaviour that is discretionary, not directly or explicitly recognized by the formal reward system, and that in the aggregate promotes the effective functioning of the organization". Most scholars understand OCB as employees' voluntary behaviour or willingness to go beyond formal employment requirements in order to contribute to organizational effectiveness, despite their being no formal rewards or additional monetary compensation offered [72][73][74]. Scholars have grouped 30 different employee behaviours considering acts of OCB into seven overstretching themes, as follows: (a) Helping behaviours; (b) sportsmanship; (c) organizational loyalty; (d) organizational compliance; (e) individual initiation; (f) civic virtue; and (g) self-development [75,76].…”
Section: Psychological Empowerment and Ocbmentioning
confidence: 99%
“…It is the ability to give advice for decision making. Alzayed, Jauhar, and Mohaidin (2017) state that what the organization wants to gain from staff is the sacrifice of time to work and not waste time on personal things and pay attention to follow the rules and regulations placed by the organization and not to neglect responsibility, when faced with obstacles, and to seek for solutions with emotional control; having no conflict with colleagues, welcome changes and help the organization and offer suggestions for organizational development toward better efficiency (Carter, Mossholder, Feild, & Armenakis, 2014;Ölçer, Florescu, & Năstase, 2014). If all the personnel are satisfied in their job, perceived justice in organization and have trust in the organization, these factors would lead to the reflection of organizational citizenship behavior.…”
Section: Organizational Citizenship Behaviormentioning
confidence: 99%